Axonal Degeneration in Tauopathies: Disease Relevance and Underlying Mechanisms - Kneynsberg, Andrew; Combs, Benjamin; Christensen, Kyle; Morfini, Gerardo; Kanaan, Nicholas M. (Frontiers in Neuroscience, 2017)
Tauopathies are a diverse group of diseases featuring progressive dying back neurodegeneration of specific neuronal populations in association with accumulation of abnormal forms of the microtubule-associated protein tau. It is well established that the clinical symptoms characteristic of tauopathies correlate with deficits in synaptic function and neuritic connectivity early in the course of disease, but mechanisms underlying these critical pathogenic events remain largely unknown. Biochemical in vitro evidence fueled the widespread notion that microtubule stabilization represents tau’s primary biological role and that the marked atrophy of neurites observed in tauopathies results from loss of microtubule stability. However, this notion contrasts with the mild phenotype associated with tau deletion. Instead, an analysis of cellular hallmarks common to different tauopathies, including aberrant patterns of protein phosphorylation and early degeneration of axons, suggests that alterations in kinase-based signaling pathways and deficits in axonal transport associated with such alterations contribute to the loss of neuronal connectivity triggered by pathogenic forms of tau. Here, we review a body of literature providing evidence that axonal pathology represents an early and common pathogenic event among human tauopathies. Observations of axonal degeneration in animal models of specific tauopathies are discussed and similarities to human disease highlighted. Finally, we discuss potential mechanistic pathways other than microtubule destabilization by which disease-related forms of tau may promote axonopathy.